The Relationship Of Diet Compliance With Blood Sugar Levels In Type 2 Diabetes Mellitus Patients - Etin Suryatin; Siti Rohimah; Nina Rosdiana (Asy-Syifa : Journal of Science and Technology Nursing, 2023)
Purpose: This study aims to determine the relationship between dietary adherence and blood sugar levels in patients with type 2 diabetes mellitus at the UPTD Panawangan Health Center.  Methods: This research method uses a cross-sectional study approach, with a sample of 80 respondents, as well as a proportional random sampling technique, and the measuring the instrument used is a questionnaire and a digital blood sugar checker (Easy Touch GCU 3 in 1). Results: The results of the analysis of this study showed that most of the respondents adhered to the diet as many as 41 people, did not comply as many as 39 people. The results of the statistical analysis of Rank Spearman obtained that Ha could be accepted. Conclusion: This study concludes that there is a relationship between dietary adherence and blood sugar levels in diabetes mellitus patients at the UPTD Panawangan Health Center, Ciamis Regency.